Engineering hairy cellulose nanocrystals for chemotherapy drug capture. (March 2022) - Young, Sarah A.E.; Muthami, Joy; Pitcher, Mica; Antovski, Petar; Wamea, Patricia; Murphy, Robert Denis; Haghniaz, Reihaneh; Schmidt, Andrew; Clark, Samuel; Khademhosseini, Ali; Sheikhi, Amir
Abstract: Cancer is one of the leading causes of death worldwide, affecting millions of people every year. Although chemotherapy remains one of the most common cancer treatments in the world, the severe side effects of chemotherapy drugs impose serious concerns to cancer patients. In many cases, the chemotherapy can be localized to maximize the drug effects; however, the drug systemic circulation induces undesirable side effects. Here, we have developed a highly efficient cellulose-based nanoadsorbent that can capture more than 6, 000 milligrams of doxorubicin (DOX), one of the most widely used chemotherapy drugs, per gram of the adsorbent at physiological conditions. Such drug capture capacity is more than 3, 200% higher than other nanoadsorbents, such as DNA-based platforms. We show how anionic hairy cellulose nanocrystals, also known as electrosterically stabilized nanocrystalline cellulose (ENCC), bind to positively charged drugs in human serum and capture DOX immediately without imposing any cytotoxicity and hemolytic effects. We elucidate how ENCC provides a remarkable platform for biodetoxification at varying pH, ionic strength, ion type, and protein concentration. The outcome of this research may pave the way for developing the next-generation in vitro and in vivo drug capture additives and devices. Graphical abstract: Image 1 Highlights: Nanoengineered cellulose provides a super-capacity drug nanoadsorbent. Dicarboxylated hairy cellulose nanocrystals capture >6, 000 mg of doxorubicin per gram. The drug capture capacity is three orders of magnitude higher than DNA. Hairy nanocelluloses provide a remarkable platform for biodetoxification. Hairy nanocelluloses may enable next-generation drug capture devices.